PEMODELAN WIND TURBINE ROTOR TIPE HAWT (HORIZONTAL AXIS WIND TURBINE) MENGGUNAKAN METODE VOLUME HINGGA - Zahroh, Millatuz; Dafik, D; Fatahillah, Arif (KadikmA, 2015)
Abstract. A Wind turbine is a wind energy converters tool into electrical energy. To optimize the electrical energy converted, it needs for further research on wind turbine process. In this research, the analysis part of wind turbine is rotor, which is the contacted part to the wind. Type of wind turbine that will be analyzed in this study is HAWT (Horizontal Axis Wind Turbine) type because this model is the most often used type and can produce great electrical energy. This research construct a model of the air flow field form of wind turbine rotor and solve these problems by using the finite volume method. Model simulation process will be done by using MATLAB and FLUENT software. The analysis was performed with the variation initial velocity level of wind. It is 3 m/s, 5 m/s, and 7 m/s. The simulation results showed that the velocity of rotation wind turbine rotor blade higher when the initial wind velocity increases. Beside that, the result is when the initial wind velocity of 7 m/s and 5 m/s, the velocity of rotation wind turbine rotor blade tend to be more stable. With 5 m/s of wind velocity to wind turbine rotor, The difference between an average direct calculation and a SOR iterative calculation is obtained the value of relative error less than 0.1%. it is 0.079%. So the finite volume method of numerical methods is effective to solve this problem. Key Words : Electrical Energy, Finite Volume Method, Velocity, Wind Turbine,.